Association between mitochondrial DNA D-loop region polymorphisms and endometriosis in a Chinese population - Li, Xinyuan; Ji, Dongmei; Marley, Jordan Lee; Zou, Weiwei; Deng, Xiaohong; Cao, Yu; Zhang, Zhiguo; Liu, Yajing; Wei, Zhaolian; Zhou, Ping; Cao, Yunxia (Journal of assisted reproduction and genetics, 2020)
Objective To investigate the correlation between endometriosis and mitochondrial DNA (mtDNA) D-loop single nucleotide polymorphisms (SNPs) and haplotype, as well as the predictive power of certain SNPs in reproductive outcomes in a Chinese Han population. Methods A case-control study was conducted in which 125 endometriosis patients and 124 controls were recruited from an academic fertility center. The entire 1124-bp D-loop region of mtDNA of whole blood samples from all subjects was amplified, sequenced, and compared with the revised Cambridge Reference Sequence (rCRS) to identify SNPs and haplotypes. The association between D-loop SNPs and embryo quality and clinical outcome following in vitro fertilization (IVF) was also assessed. Results A total of 321 polymorphisms were identified by sequencing, allowing comparison of the D-loop between endometriosis patients and controls. The frequency of the AC523–524 del, T16172C, and C16290T variants were significantly higher, while the frequency of polymorphisms T195C, 573XCins, 16036Gins, 16049Gins, T16140C, A16183C, T16189C, and 16193Cins were lower, in the endometriosis group compared with the control group ( p < 0.05). Within the endometriosis group, the high-quality blastocyst rate in the 16,290T subgroup was significantly lower than that in the 16290C subgroup ( p < 0.05). In the control group, 16519C carriers showed a lower rate of high-quality blastocyst development compared with 16519T ( p < 0.05). In endometriosis patients clinical pregnancy rate was significantly lower in the 150T subgroup compared with the 150C subgroup ( p < 0.05). Discussion Data confirms a correlation between D-loop polymorphisms and endometriosis. The polymorphisms AC523–524 del, T16172C, and C16290T are associated with increased risk of endometriosis, while T195C, 573XCins, 16036Gins, 16049Gins, T16140C, A16183C, T16189C, and 16193Cins are associated with decreased risk of endometriosis. In addition, C16290T and T16519C can be associated with poor quality blastocyst development in population with and without endometriosis, respectively and C150T can be a predictor of poor IVF outcome.